Measured Pulmonary and Systemic Markers of Inflammation and Oxidative Stress Following Wildland Firefighter Simulations. Issue 4 (April 2016) - Ferguson, Matthew D.; Semmens, Erin O.; Dumke, Charles; Quindry, John C.; Ward, Tony J.
Abstract : Objective: A controlled human exposure study was conducted to investigate the impact of inhalational exposures to wood smoke PM2.5 on measured concentrations of airway and systemic inflammatory biomarkers. Methods: Mimicking wildland firefighter activities, 10 participants were exposed to three doses of wood smoke PM2.5 (filtered-air, 250 μg/m 3, and 500 μg/m 3 ) while exercising on a treadmill. Exhaled breath condensate (EBC) and blood plasma samples were obtained pre-, immediately post-, and 1-hour postexposure. 8-isoprostane, pH, and myeloperoxidase were measured in EBC, while H2 O2, surfactant protein D, and pentraxin-3 (PTX3) were measured in both EBC and plasma. Results: Only pH, 8-isoprostane, and PTX3 displayed significant changes when comparing pre- and postexposures. Conclusions: Markers of inflammation and oxidative stress, including PTX3, pH, and 8-isoprostane in EBC and/or plasma, are sensitive to wood smoke inhalation, with further investigations warranted.